2020
DOI: 10.1186/s12935-020-01577-1
|View full text |Cite
|
Sign up to set email alerts
|

LINC01006 facilitates cell proliferation, migration and invasion in prostate cancer through targeting miR-34a-5p to up-regulate DAAM1

Abstract: Background Prostate cancer (PCa) is a kind of malignancy occurring in the prostate gland. Substantial researches have proved the major role of long noncoding RNAs (lncRNAs) in PCa. However, the role of long intergenic non-protein coding RNA 1006 (LINC01006) in PCa has not been investigated yet. Methods RT-qPCR was used to examine the expression levels of LINC01006 and its downstream targets. The function of LINC01006 in PCa was tested by in vitro and in vivo assays. With application of RNA pull down, RNA imm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
(31 reference statements)
2
8
0
Order By: Relevance
“…For example, a study has manifested that miR-34a is a possible onco-suppressor for HCC [ 14 ]. In the meantime, miR-34a also could be regarded as a suppressor of lots of cancers including HCC, ovarian cancer and prostate cancer [ 15 17 ]. A study has revealed that up-regulated miR-34 in hepatic stellate cells relieves the progression of liver fibrosis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study has manifested that miR-34a is a possible onco-suppressor for HCC [ 14 ]. In the meantime, miR-34a also could be regarded as a suppressor of lots of cancers including HCC, ovarian cancer and prostate cancer [ 15 17 ]. A study has revealed that up-regulated miR-34 in hepatic stellate cells relieves the progression of liver fibrosis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In pancreatic cancer and prostate cancer, LINC01006 promotes cell growth and metastasis, providing a novel target for cancer therapy. 17 , 18 A recent study about cervical cancer showed LINC01006 downregulation not only inhibited the proliferation and metastasis of cervical cancer cells but also promoted cell apoptosis. 17 In this study, LINC01006 exhibits tumor‑promoting functions in colon cancer and provides the basis for identifying LINC01006 as targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…LINC01006 is upregulated in prostate ( 20 ) and pancreatic ( 21 ) cancers and plays pro-oncogenic roles. By contrast, this lncRNA is weakly expressed in gastric cancer and exhibits a notable association with age, tumor location, tumor size and venous invasion ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed the abnormal expression of the long intergenic non-protein-coding RNA 1006 (LINC01006) in prostate ( 20 ), pancreatic ( 21 ) and gastric ( 22 ) cancers. However, whether LINC01006 plays important roles in cervical cancer remains unclear.…”
Section: Introductionmentioning
confidence: 89%